Light-adaptable artificial iris with dynamically scalable pupil-aperture function by radially patterned photochromic transition control - Nauman, Asad; Choi, Jun-Chan; Cho, Young-Min; Lee, Jae-Won; Na, Jun-Hee; Kim, Hak-Rin (Elsevier BV, 2024)
The iris is an ocular organ that actively controls the size of the pupil-aperture in response to external light, thereby regulating the amount of light reaching the retina for better visual acquisition. Herein, we propose a light-adaptive pupil-scalable artificial iris for addressing human iris defects with biomimetic self-regulating light control similar to human iris actuation, which is realized by a radially gradient and reversible photoswitching of photochromic dyes doped within a biocompatible hydrogel matrix. The radial photochromic switching of light transmissions was achieved by the gradient patterning of the crosslinking density of the hydrogel matrix using a near-infrared light-absorbing photomask that generated radially thermal gradience during hydrogel matrix polymerization. With the effective pupil-aperture control, the proposed artificial iris exhibited a variation in the visible-light transmittance from -82 % at the ultraviolet light (UV) intensity of 0.5 mW/cm2 to -43 % at 3.0 mW/cm2 representing the transparent and colored states, respectively. The switching times for the transitions to the colored and transparent states were 27.42 and 112.25 s, respectively, at a UV intensity of 3.0 mW/cm2, which can be faster under the hydrated state. The artificial iris demonstrated potential in biomedical applications by offering reliable light-adaptive attenuation control through human-like pupil-aperture adjustments.